2017
DOI: 10.1007/s11223-017-9900-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analysis of Springback Behavior of Aluminum Alloys

Abstract: Presented work deals with springback behavior of two different aluminum alloys, one falling into 5th series (AW-5754 H22) with a thickness of 0.8 mm and other from 6th series (AW-6082 T6) with 1.0 mm thickness. These materials are used for their various applications and hardening process. The springback behavior was investigated by U-bending test. Bending tool was graduated jig with rollers and experiment was performed on R11 and R17 radii. The first series of specimens were oriented in a parallel direction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Also in the industries which produce stampings, such as the automotive industry, accurate predictions of forming process, including stress-strain distribution, springback and thickness are necessary [10]. Today it is feasible to use finite element analysis for a more accurate prediction of the springback effect [11,12]. The finite element analysis (FEA) is a modern tool that can help to achieve more accurate springback predictions [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Also in the industries which produce stampings, such as the automotive industry, accurate predictions of forming process, including stress-strain distribution, springback and thickness are necessary [10]. Today it is feasible to use finite element analysis for a more accurate prediction of the springback effect [11,12]. The finite element analysis (FEA) is a modern tool that can help to achieve more accurate springback predictions [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that besides the Bauschinger effect and Young s modulus, there is also a great effect arising from elastic and plastic anisotropy on the results of springback predictions. The effects of the different yield criterions (Hill48 and Hill90), bending radii and directions on the aluminium alloys springback are described by Slota et al [48].…”
Section: Introductionmentioning
confidence: 99%
“…Spring-go or spring-back phenomena were investigated on different materials by Thipprakmas et al [14], Ouakdi et al [22], Hakan et al [24], Syeed et al [27], Krinninger et al [29], Slota et al [34] using nite element m e t h o d a n d / o r t h r o u g h e x p e r i m e t s . Lawanwomg et al tried [26] to eliminate spring-back by employing a novel technology in HSS sheet U-die bending where the bottom plate was additionaly bent with a counterpunch at the nal stage of U-bending.…”
Section: Introductionmentioning
confidence: 99%